2005
DOI: 10.1097/01.tp.0000168090.19875.b0
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Short- and Long-term Survival of Primary Cadaveric Renal Allografts in Pediatric Recipients: A UNOS Analysis

Abstract: The short-term graft survival rate of pediatric cadaveric kidney transplants has significantly improved, yet the long-term outcome has changed little. The long-term outcomes for teenagers (13-20 yrs), patients with FGS, and African-Americans lag significantly behind other groups. In order to improve long-term graft survival in these high-risk patients, newer preventive or treatment strategies must be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 17 publications
(12 reference statements)
3
48
0
1
Order By: Relevance
“…Transplant survival was affected by age until the last decade of our study, with an increased graft loss in those transplanted before 2 years of age in the 1980s and 1990s. Age becomes important again at adolescence [9, 10, 23], when non-concordance contributes significantly to transplant loss [18, 23], an effect that we saw in our patients, although this did not reach statistical significance during the last decade.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Transplant survival was affected by age until the last decade of our study, with an increased graft loss in those transplanted before 2 years of age in the 1980s and 1990s. Age becomes important again at adolescence [9, 10, 23], when non-concordance contributes significantly to transplant loss [18, 23], an effect that we saw in our patients, although this did not reach statistical significance during the last decade.…”
Section: Discussionmentioning
confidence: 46%
“…UK transplant data [23] demonstrated an increased risk of early transplant loss, principally due to technical difficulties, in those <2 years of age, although after this time graft loss was equal to that of older children. More recent UNOS data [9] have shown that younger age and earlier era of transplant adversely affect transplant outcome and give an odds ratio of 2 for increased risk of graft loss in 2- to 5-year-olds in comparison with 6- to 12-year-old children. Transplant survival was affected by age until the last decade of our study, with an increased graft loss in those transplanted before 2 years of age in the 1980s and 1990s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal allograft survival in infants is now similar to that in older children [7,8], and short-term deceased donor allograft survival in children now approaches that of living donation [7,8]. Three-and five-year graft survival rates in children have been shown to be related to the transplant center, recipient race, recipient age, primary disease, date of transplant, panel reactivity (PRA), and donor source [5,9]. The half-life of renal allografts in pediatric patients is now about 10 years [10]; therefore, it is important to explore the factors related to long-term, greater than 10 year, allograft survival.…”
Section: Introductionmentioning
confidence: 96%
“…Renal allograft survival in children has improved substantially over the last two decades, with several large registry studies reporting graft survival approaching 80% at 3 years and 75% at 5 years [1][2][3][4][5]. A single center study reported 66% graft survival at 10 years [6].…”
Section: Introductionmentioning
confidence: 99%